Polyphenols for improvement of inflammation and symptoms in rheumatic diseases: systematic review - Coletro, Hillary Nascimento; Diniz, Amanda Popolino; Guimarães, Nathália Sernizon; Carraro, Júlia Cristina Cardoso; Mendonça, Raquel de Deus; Meireles, Adriana Lúcia (São Paulo Medical Journal, 2021)
BACKGROUND: Rheumatic diseases (RDs) are a group of pathological conditions characterized by inflammation and functional disability. There is evidence suggesting that regular consumption of polyphenols has therapeutic effects capable of relieving RD symptoms. OBJECTIVE: To synthesize data from randomized controlled trials on administration of polyphenols and their effects on RD activity. DESIGN AND SETTING: Systematic review conducted at Universidade Federal de Ouro Preto, Minas Gerais, Brazil. METHODS: A systematic search was conducted in the databases PubMed (Medline), LILACS (BVS), IBECS (BVS), CUMED (BVS), BINACIS (BVS), EMBASE, Web of Science and Cochrane Library and in the grey literature. The present study followed a PRISMA-P checklist. RESULTS: In total, 646 articles were considered potentially eligible, of which 33 were then subjected to complete reading. Out of these, 17 randomized controlled trials articles were selected to form the final sample. Among these 17 articles, 64.71% assessed osteoarthritis (n = 11), 23.53% rheumatoid arthritis (n = 4), 5.88% rheumatoid arthritis and fibromyalgia (n = 1) and 5.88% osteoarthritis and rheumatoid (n = 1). Intake of polyphenol showed positive effects in most of the studies assessed (94.12%): it improved pain (64.70%) and inflammation (58.82%). CONCLUSION: Polyphenols are potential allies for treating RD activity. However, the range of polyphenol sources administered was a limitation of this review, as also was the lack of information about the methodological characteristics of the studies evaluated. Thus, further primary studies are needed in order to evaluate the effects of polyphenol consumption for reducing RD activity. SYSTEMATIC REVIEW REGISTER: PROSPERO - CRD42020145349.